The principle of common heritage of humankind and the BBNJ agreement - Scovazzi, Tullio (2025)
Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas beyond National Jurisdiction (New York, 2023) it addresses marine biodiversity under the perspective of four subject-matters: marine genetic resources, area-based management tools, environmental impact assessment and transfer of marine technologies. This article takes in consideration only the first subject, which involves two fundamental principles of international law of the sea, one having a consolidated tradition (the freedom of the sea) and the other having an innovating character (the common heritage of humankind).